THE ETIO-PATHOGENESIS OF PERIODONTAL DISEASE - Mustaqimah, Dewi Nurul (Institute of Topical Disease Universitas Airlangga, 2010)
The etiology of polymicrobial disease such as periodontitis is likely to be more complex than suggested by the traditional paradigm of disease involving a single virulent organism which up to now has been believed. This review limits its discussion to the other subgingival microbiota which is not yet cultivable, however it is suggested be implicated with the severity of periodontal disease. The intricate interactions between viruses and bacteria within periodontal pockets as a co-infection process reveal its role in the etio-pathogenesis of periodontal disease. Also Archaea domain participate in syntrophic relationship with the microbiota life members in the subgingival crevice, promote colonization by special bacterial group during periodontitis. It is clear that periodontal diseases are not monoinfections.